Kan et frivilligt samleje være strafbart? - Clara Juul Holm (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract: This article examines some conceptual challenges associated with the content and possible demarcation of the notions of consent and voluntariness in recent Danish legislation on rape. It is argued that free will or voluntariness, and the expression thereof, should be seen as occurrences on a spectrum, and that the expression of consent or free will is at least partially necessary if such subjective concepts are to be useful in a legal context. The paper examines some general implications of this for possible  outcomes of case law. Uncertainties include what should be made of the use of the »presumptions« mentioned in the bill. Some implications for the evaluation of a defendant’s mens rea are also touched upon. It is concluded that the Danish court enjoys a margin of discretion that allows it the ability to criminalise instances of intercourse even when they are not necessarily non-voluntary.